Van Rij en Stam Rapporten van de Commissie van onderzoek naar beweerde excessen gepleegd door Nederlandse militairen in Indonesië, 1949-1954 - van der Bent, Maarten (Amsterdam University Press, 2022)
During the Indonesian war of independence, reports of alleged war crimes by Dutch soldiers penetrated the Netherlands only sparsely. Even so, it was during the war that the first calls for an independent investigation into such reports were heard. After repeated calls from the Tweede Kamer, a commission of three lawyers was finally sent to Indonesia in October 1949 with the task of carrying out a non-judicial investigation into the allegations of extreme violence. For various reasons, this enquiry commission submitted reports on only two cases, which were only signed by two of the three commission members, Kees van Rij and Wim Stam. Until 1969, the existence of these reports remained hidden from parliament and the outside world. During the preparation of the 'Excessennota', the reports resurfaced and never filed reports on six other cases were found. All eight reports played a crucial role in the drafting of the note, while the report on South Sulawesi in particular would prove of great importance for the historiography of the war. Up until now, the reports by Van Rij and Stam had been hidden deep in the archives. This source publication, preceded by an extensive introduction, makes them accessible to a wider public for the first time.